A convolutional autoencoder architecture for robust network intrusion detection in embedded systems - Borgioli, Niccolò; Aromolo, Federico; Thi Xuan Phan, Linh; Buttazzo, Giorgio (Journal of systems architecture, 2024)
Security threats are becoming an increasingly relevant concern in cyber–physical systems. Cyber attacks on these systems are not only common today but also increasingly sophisticated and constantly evolving. One way to secure the system against such threats is by using intrusion detection systems (IDSs) to detect suspicious or abnormal activities characteristic of potential attacks. State-of-the-art IDSs exploit both signature-based and anomaly-based strategies to detect network threats. However, existing solutions mainly focus on the analysis of statically defined features of the traffic flow, making them potentially less effective against new attacks that cannot be properly captured by analyzing such features. This paper presents an anomaly-based IDS approach that leverages unsupervised neural models to learn the expected network traffic, enabling the detection of unknown novel attacks (as well as previously-known ones). The proposed solution uses an autoencoder to reconstruct the received packets and detect malicious packets based on the reconstruction error. A careful optimization of the model architecture allowed improving detection accuracy while reducing detection time. The proposed solution has been implemented on a real embedded platform, showing that it can support modern high-performance communication interfaces, while significantly outperforming existing approaches in both detection accuracy, inference time, generalization capability, and robustness to poisoning (which is commonly ignored by state-of-the-art IDSs). Finally, a novel mechanism has been developed to explain the detection performed by the proposed IDS through an analysis of the reconstruction error.